Pertumbuhan Semai Mahoni (Swietenia macrophylla) pada Media Tailing dengan Penambahan Arang Tempurung Kelapa dan Pupuk Kompos - Basuki Wasis; Mumtazul Fikri (Jurnal Silvikultur Tropika, 2022)
Mining activities can be causing negative effect to the environment if its waste (tailing) not well managed. An effort that can be applied to rehabilitate damaged land is post-mining land revegetation with fertilizer application. It can be performed with the addition of coconut shell charcoal and compost. The appropriate plant spesies in post-mining land is mahagony (Switenia macrophylla). This research aimed to determine the effect of coconut shell charcoal and compost addition on the growth of mahagony seedlings and determine the well dose of coconut shell charcoal and compost addition to the mahagony seedlings in the post-mining media (tailing). The experimental design used in this research was factorial Completely Randomized Design (CRD). It consists of two factors, first factor was coconut shell charcoal addition which consists of 4 levels and the second factor was compost addition which consists of 5 levels, each level consists of three replication. The research’s results showed that the addition of coconut shell charcoal and compost significantly affected to wet weight, dry weight and the ratio of mahagony seedlings root shoots parameters. The best dose combination to the mahagony seedlings in the tailing medium was the A2B4 treatment (1000 g tailing, 40 g coconut shell charcoal and 100 g compost). Keywords: coconut shell charcoal, compost, revegetation, Swietenia macrophylla, tailing